Konseptualisasi Model Digital Marketing Produk Kopi Guna Mendukung Ketahanan Pangan Berkelanjutan di Desa Garahan - Hardiani Kusuma, Ajeng Pramesthy; Halimatus Sa’diyah; Jumantoro, Tegar Raffi Putra (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
Garahan Village, located in Silo District, Jember Regency, is known for its community-based coffee production. However, the local farmers continue to face significant challenges in marketing their coffee products beyond the village level. The lack of knowledge and skills in digital marketing strategies has resulted in limited market access and low product competitiveness. This community service program was designed to address these challenges by enhancing the marketing capabilities of local coffee farmers through the conceptualization and implementation of a digital marketing model. The ultimate goal is to support sustainable food security by strengthening the economic resilience of coffee farmers. The activities in this program involved a series of stages, including preliminary surveys to identify key problems, direct observations, educational outreach on the importance of digital marketing, hands-on training in social media utilization and online marketplace platforms, and continuous monitoring and evaluation of the implementation process. The main partners of this initiative were members of the local coffee farmer group in Garahan Village. The results of the program indicate a significant improvement in the partners’ understanding and application of digital marketing tools. Prior to the intervention, only 10% of participants were familiar with digital marketing; this figure rose to 85% after the training sessions. Moreover, digital-based coffee sales increased by 40% within three months following the intervention. These outcomes demonstrate the effectiveness of the community engagement approach in addressing local agricultural marketing issues. Key outputs of the program include the establishment of social media accounts and online storefronts for coffee products, increased farmer capacity in managing digital promotion, and the production of a simple digital marketing guidebook for sustainable use.